VUV excitation properties of LnAl(3)B(4)O(12): Re (Ln = Y, Gd; Re=Eu, Tb) - You, HP; Hong, GY; Zeng, XQ; Kim, CH; Pyun, CH; Yu, BY; Bae, HS (PERGAMON-ELSEVIER SCIENCE LTD, 2000)
Vacuum ultraviolet excitation spectra of LnAl(3)B(4)O(12):Re (Ln = Y, Gd; Re = Eu, To), along with X-ray photoelectron spectra, were measured. The spectra are tentatively interpreted in terms of the optical properties of the rare earth ions and the band structure. It was found that there is an energy transfer from the hosts to the rare earth ions. It was also found that the top of the valence band in the Gd compound is mainly formed by the 2p levels of O2- and the 4f levels of Gd3+, and in the Y compound mainly by the 2p levels of O2-. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: PHOSPHORS; IONS; LUMINESCENCE; TRANSITIONS; ABSORPTION; CRYSTALS; UV